Study on red edge characteristics of rice spectral caused by nitrogen level - WANG Xiu-zheng; WANG Ren-chao; LI Yun-mei; SHEN Zhang-quan (浙江大学学报. 农业与生命科学版)
The canopy spectra of rice under different nitrogen levels were studied. Some red edge parameters in the first derivative reflectance curve (wavelength, amplitude and area of the red edge peak) were studied to evaluate rice leaf chlorophyll, LAI etc. Red edge positions move to longer wave bands till booting stage and move to short bands after booting stage. A high correlation was found between chlorophyll a content of top leaves and the wavelength of the red edge position and between LAI and the red edge parameter. Then, the red edge was found valuable for assessment of rice up stand leaves chlorophyll contents. But a correlation was not found between chlorophyll b content of leaves or carotenoid or albumen-nitrogen or non-albumen-nitrogen and the wavelength of the red parameters. Some red edge parameters are one of the best remote sensing descriptors.